Efektivitas Pemenjaraan Ditengah Ide Pemidanaan Dengan Pendekatan Keadilan Restoratif - Diah Ratna Sari Hariyanto; I Dewa Gede Dana Sugama (University of Udayana, 2021)
The present study seeks to find out, examine the effectiveness of criminal sanctions in the form of imprisonment in Bali, as well as discover the basis for the application of punishment with a restorative justice approach. This study belongs to empirical legal research that is descriptive in nature and makes the Correctional Institution in Bali the object of research. The results of the study suggested that the emergence of recidivists in Bali and the still negative stigma among the Balinese community subsequent to the removal of prisoners shows that correctional goals are still unachieved and the emergence of recidivists in Bali implies that the criminal sanction in the form of imprisonment still remains ineffective. The concept of an ideal criminal system to be applied in Bali related to imprisonment is the one adopting the restorative justice approach, because in addition to minimising imprisonment, in this approach, the interests of victims are more concerned by making various efforts to resolve conflicts and by making rehabilitation. Tujuan dari studi ini untuk mengetahui dan menganalisis efektivitas pemenjaraan di Bali dan menemukan landasan penerapan pemidanaan dengan pendekatan keadilan restoratif. Penelitian ini adalah penelitian hukum empiris yang sifatnya deskriptif dan menjadikan Lembaga Pemasyarakatan di Bali sebagai objek penelitian. Hasil studi menunjukkan bahwa munculnya residivis di Bali dan masih adanya stigma negatif dari masyarakat Bali setelah narapidana keluar dari lapas menunjukkan bahwa tujuan pemasyarakatan belum tercapai dan sanksi penjara tidak efektif di Bali. Konsep sistem pemidanaan yang ideal untuk diterapkan di Bali terkait dengan pemenjaraan adalah konsep sistem pemidanaan dengan pendekatan restorative justice yang memperhatikan kepentingan korban dengan melakukan berbagai upaya penyelesaian konflik dan rehabilitasi, serta meminimalisasi penjatuhan pidana penjara.